Integrating Energy Markets in the Wider Europe: The Eastern Dimension1 - Elias Kolovosa, Afroditi Semkoua; Anna Konstantinidou, Ilias Andreadisa (European Journal of Sustainable Development, 2019)
This paper examines the extent of integration between the regional energy markets of the Member States of the European Union and the countries of the wider Europe with special attention to the Eastern Partnership. Therefore, whether the aforementioned energy markets are in a position to conform to the acquis communautaire and ensure the security of energy supply to the EU in affordable prices. We will record what needs to be done for the integration of these regional energy markets with the EU common market and specifically: (a) the legal framework of the Eastern European non-EU regional energy markets, from the perspective of energy, trade and free competition. The impediments integration is facing and under which circumstances can it be achieved. (B) The required infrastructure and connectivity networks necessary to be completed in order to allow the utilization of the energy reserves in the third countries and the network connection of these third countries with the EU. The designated Trans European Network Strategy regarding the sectors of electricity, natural gas, oil and the Projects of Common Interest currently being constructed in Eastern Europe. (C) The promotion of investments that needs to be carried out in the wider European countries in order to ensure security of energy supply of the EU in the long term. The various forms of cooperation agreements between Georgia, Moldova, Ukraine, Armenia, Belarus and Azerbaijan with the EU and their contribution to the promotion of energy investments and the interconnection of cooperation agreements with the Energy Community. Keywords: EU, Eastern Europe, Free Trade Agreements, Infrastructure, TEN – E, PCI, Promotion of Investments